Effect of poisson ratio on cellular structure formation - Bischofs-Pfeifer, Ilka; Schwarz, Ulrich S. (Arxiv, 2005)
Mechanically active cells in soft media act as force dipoles. The resulting elastic interactions are long-ranged and favor the formation of strings. We show analytically that due to screening, the effective interaction between strings decays exponentially, with a decay length determined only by geometry. Both for disordered and ordered arrangements of cells, we predict novel phase transitions from paraelastic to ferroelastic and anti-ferroelastic phases as a function of Poisson ratio.
Gesehen am 15.12.2017